UN Security Council Resolutions in the Legal System: Lesson Learned from Singapore - Kurniaty, Rika; Widagdo, Setyo; Ruslijanto, Patricia Audrey; Suryokumoro, Herman (Brawijaya Law Journal, 2022)
United Nations (UN) Security Council (UNSC) resolutions (UNSCRs) are adopted by a vote of the five permanent members and ten non-permanent members of the UNSC. Each UNSCR is understood to be part of the “primary responsibility for the maintenance of international peace and security” of the UN. The Indonesian government has been encouraged by various parties to make a legal instrument that would enforce the UNSCRs. Such an instrument would serve to bridge and reduce gaps in the rule of law regarding the enforcement of UNSCRs for nations. However, the government of Indonesia faces several challenges in implementing legal instruments for the UNSCRs. This article maintains that it is crucial to study accommodative policies regarding the national enforcement of UNSCRs by considering the example of Singapore. Singapore has special laws that respond to UNSCRs (The UN Act Chapter 339-UN Act). UN Act 339 is the legal umbrella in Singapore for the government’s implementation of UNSCRs. The UN Act is also an attempt by the Singaporean government to carry out its international obligations to the United Nations.